The effect of behavioral rehearsal technique through group counseling for overcoming social anxiety of students - Saman, Abdul; Bakhtiar, Muhammad Ilham (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
This research examined the influence of group counseling using behavioral rehearsal techniques to overcome students’ social anxiety. This research used the quantitative method with a quasi-experimental design namely Matching-Only Design. The study involved 30 students for the control group and 30 students for the experimental group selected through purposive sampling. Data were collected using a questionnaire that had been validated. They were then analyzed using normality testing, homogeneity, data nominality testing, gain score and hypothesis testing. The findings of this research indicated that group counseling through behavioral rehearsal techniques could overcome the problem of social anxiety experienced by students. In the pretest, the research showed that the social anxiety level of students in the experimental group was in the high category, and the control group was in the medium category. While the posttests of both experimental and control groups were in the very low category. Behavioral rehearsal techniques should be informational and practical in the development of knowledge, especially in dealing with the problems of social anxiety.